ZONASI PERGERAKAN TANAH DI DESA PANYUTRAN DAN SEKITARNYA, KECAMATAN PADAHERANG, KABUPATEN PANGANDARAN, PROVINSI JAWA BARAT - Jhon Pengarapen Barus; Nana Sulaksana; Zufialdi Zakaria (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2022)
The research area located in Panyutran Village and its surroundings are areas whose surface is covered by Tertiary-aged rocks. In the study area, the constituent rock types are volcanic breccia, tuff and limestone. The method of studio analysis approach with remote sensing is the lineament analisys, lineament structure, slope, rock strength, mountain front sinuosity (Smf), and the ratio of the width of the valley floor to the height of the valley (Vf). The results of the analysis of these aspects indicate that the research area has an area with high or unstable ground movement susceptibility 2.3%, medium tectonic activity vulnerability 86.3% and low or stable ground movement vulnerability 11.4%. The results of the morphotectonic analysis show that the research area has medium tectonic activity.